PENGARUH KEPERCAYAAN, KEMUDAHAN DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DI APLIKASI SHOPEE - Subagyo; Tukidi; Indah WV (Jurnal Manajemen, 2019)
This research aims to determine the impact of trust, easiness, and quality information on purchasing decisions online in the Shopee app. The method used in this research is the quantitative method and assessment of the results based on respondents ' answers using a Likert scale. The population in this study is all consumers of Satya Negara Indonesia University student A and the samples in this study amounted to 100, and the sampling Tekhnik used in this study was Probability Sampling, and Sample determination based on simple random sampling. The data analysis methods used in the study are test instruments (validity and reusability), Data normality analysis, assumption Test (normality, multicholinerity, heterokedastisity, autocorrelation), correlation coefficient test, linear regression test Multiple, F-Test, T-Test, and coefficient of determinant (R ²).The results showed that simultaneously (test F) showed that there was a significant influence between the trust variables (X1), the easiness (X2), and the quality of information (X3) against the purchase decision (Y). Partial (T-Test) the trust is influential as positive to the purchase decision, whereas the easiness variable does not affect as positive to the purchase decision, and the information quality has effect as negative to Purchase decision.